2022
DOI: 10.53730/ijhs.v6ns10.13613
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of adverse drug reaction and its outcome among patients in tertiary care hospital, Uttar Pradesh

Abstract: Introduction: World Health Organization defines adverse drug reactions (ADRs) as any noxious, unintended, and undesired effect of a drug, which occurs at doses used in humans for prophylaxis, diagnosis, or therapy. For evaluating the incidence and outcome of adverse drug reactions (ADRs) to assist in minimizing the deleterious effects, the present study was planned to find the incidence of ADR, its severity, and outcomes among patients. Material and Methods: The spontaneous ADR reporting technique and the Susp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
1
0
0
Order By: Relevance
“…There was an another study reported a lower incidence of 3.7% ADRs among hospitalized patients in India, highlighting the need to investigate the reasons for this discrepancy, including under-reporting and inadequate pharmacovigilance systems 22 . In our study, the majority of adverse drug reactions (ADRs) were classified as Type A according to Rawlins and Thompson's classification, consistent with the established observation that approximately 80% of ADRs fall into this category, while the remaining 20% are categorized as Type B 23 . This finding is further substantiated by two additional studies 24,25 .…”
Section: Resultssupporting
confidence: 87%
“…There was an another study reported a lower incidence of 3.7% ADRs among hospitalized patients in India, highlighting the need to investigate the reasons for this discrepancy, including under-reporting and inadequate pharmacovigilance systems 22 . In our study, the majority of adverse drug reactions (ADRs) were classified as Type A according to Rawlins and Thompson's classification, consistent with the established observation that approximately 80% of ADRs fall into this category, while the remaining 20% are categorized as Type B 23 . This finding is further substantiated by two additional studies 24,25 .…”
Section: Resultssupporting
confidence: 87%